2024
DOI: 10.3389/fenvs.2023.1289142
|View full text |Cite
|
Sign up to set email alerts
|

Satellite derived trends and variability of CO2 concentrations in the Middle East during 2014–2023

Ricardo Fonseca,
Diana Francis

Abstract: The Middle East has major sources of anthropogenic carbon dioxide (CO2) emissions, but a dearth of ground-based measurements precludes an investigation of its regional and temporal variability. This is achieved in this work with satellite-derived estimates from the Orbiting Carbon Observatory-2 (OCO-2) and OCO-3 missions from September 2014 to February 2023. The annual maximum and minimum column (XCO2) concentrations are generally reached in spring and autumn, respectively, with a typical seasonal cycle amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 132 publications
0
1
0
Order By: Relevance
“…It would also be important for such models to explicitly predict the amount of dust and other pollutants in the atmosphere, which are abundantly present in the region 78 , so as to account for the impact of the atmospheric composition on the radiation, atmospheric circulation, convective activities and rainfall. An accurate representation of the spatial and temporal variability of greenhouse gasses is also paramount, as recent studies showed an increasing trend and a heterogeneous spatial pattern in the MENA region 153 , 154 .…”
Section: Discussionmentioning
confidence: 99%
“…It would also be important for such models to explicitly predict the amount of dust and other pollutants in the atmosphere, which are abundantly present in the region 78 , so as to account for the impact of the atmospheric composition on the radiation, atmospheric circulation, convective activities and rainfall. An accurate representation of the spatial and temporal variability of greenhouse gasses is also paramount, as recent studies showed an increasing trend and a heterogeneous spatial pattern in the MENA region 153 , 154 .…”
Section: Discussionmentioning
confidence: 99%
“…The swift urban expansion in the UAE could intensify air pollution sources. With surface observations sparse in this region, satellite remote sensing becomes a crucial method for air quality monitoring (Chudnovsky et al, 2014;Fonseca et al, 2023;Francis et al, 2023). What is more, satellite measurements themselves fall short in clarifying the different atmospheric processes responsible for peak pollution levels.…”
Section: Introductionmentioning
confidence: 99%